"I Was Really Pleasantly Surprised": Firsthand Experience and Shifts in Physical Therapist Perceptions of Telephone‐Delivered Exercise Therapy for Knee Osteoarthritis–A Qualitative Study. Issue 4 (28th March 2019) - Lawford, Belinda J.; Delany, Clare; Bennell, Kim L.; Hinman, Rana S.
Abstract : Objective: To explore physiotherapists' perceptions before and after delivering exercise advice via telephone to patients with knee osteoarthritis (OA). Methods: We performed a descriptive qualitative study (based on interpretivist methodology) embedded within a randomized controlled trial. Before and after providing exercise therapy to patients with knee OA, all 8 physiotherapists who were involved in the trial participated in semi‐structured interviews via telephone. Interviews were audio recorded, transcribed verbatim, and thematically analyzed. Results: Prior to delivering the intervention, physiotherapists thought that the telephone should be used only for follow‐up rather than as the primary mode of providing care. They believed that telephone‐delivered care would be convenient and cost‐saving for patients, would provide increased opportunity for patient education, and also increase access to services, but that the lack of visual and physical contact with patients would be problematic. After delivering the intervention, physiotherapists reflected that telephone‐delivered care exceeded their expectations, noting positive patient outcomes including improved pain, function, and confidence. The focus on communication allowed more personal conversations with patients and shifted patient expectations of care away from manual therapies and toward self‐management. Numerous implementation considerations were identified, including the need for clinician training in communication skills, written resources for patients to supplement telephone calls, and careful deliberation of how to schedule telephone consultations during the usual in‐person consultations in the clinic. Conclusion: Although physiotherapists were initially skeptical about the effectiveness of telephone‐delivered service models to patients with knee OA, perceptions shifted once they experienced delivery of care via this nontraditional method. Our findings suggest that firsthand experience may be necessary for physiotherapists to embrace new models of service delivery.